2021
DOI: 10.1007/s00056-021-00362-7
|View full text |Cite
|
Sign up to set email alerts
|

Erratum zu: Auswirkungen von Natriumchlorid auf das Genexpressionsprofil parodontaler Ligamentfibroblasten bei Dehnung

Abstract: The article "Effects of sodium chloride on the gene expression profile of periodontal ligament fibroblasts during tensile strain", written by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Overt infiltration and inflammatory activity of myeloid cells, in particular Mφ, is associated with PD progression and severity. P. gingivalis (Pg) and A. actinomycetemcomitans (Aa) are two key etiological bacteria involved in periodontal pathogenesis (Grenier & Tanabe, 2010; Guentsch et al, 2009; Schröder et al, 2023). Information on lncRNA involvement in PD pathogenesis and the role of periodontal bacteria in lncRNA expressional perturbation remains poorly understudied (Ahmad et al, 2023; Sayad et al, 2020; Uttamani et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Overt infiltration and inflammatory activity of myeloid cells, in particular Mφ, is associated with PD progression and severity. P. gingivalis (Pg) and A. actinomycetemcomitans (Aa) are two key etiological bacteria involved in periodontal pathogenesis (Grenier & Tanabe, 2010; Guentsch et al, 2009; Schröder et al, 2023). Information on lncRNA involvement in PD pathogenesis and the role of periodontal bacteria in lncRNA expressional perturbation remains poorly understudied (Ahmad et al, 2023; Sayad et al, 2020; Uttamani et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular Na + content in tissues can trigger the expression of the osmoprotective transcription factor NFAT5 [ 31 , 32 , 33 , 34 ]. Moreover, NFAT5 expression is increased after mechanical loading in fibroblasts [ 35 ]. Sodium MRI studies have shown a correlation between the extracellular sodium concentrations and OA-characteristic catabolic remodeling processes of the extracellular matrix [ 36 ].…”
Section: Introductionmentioning
confidence: 99%